Dakwah di Tengah Keragaman Masyarakat: Hakikat dan Strategi - Nahed Nuwairah (UIN Antasari Banjarmasin, 2014)
Creating an atmosphere of harmony in extremely diverse Indonesian society requires togetherness of various parties, including the preacher, who bear the responsibility to reflect the values of kindness in all aspects of human life. Dakwah creative and innovative approach is a challenge for the preachers who are required to observe and understand the reality of the diversity of Indonesia. This paper attempts to examine the nature of dakwah, namely freedom, rationality, and universalism within the framework of the diversity of the community in Indonesia. In addition, it also offers a model of dakwah strategies in the effort to build religiousity in the middle of the growing diversity of Indonesia, with hope in the future there are efforts to elaborate more systematically